ORGANIZATIONAL FACTOR AS BASIC ELEMENTS OF THE ESTONIAN YOUTH WORKERS´ PROFESSIONAL GROWTH - Veigel, Maarika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The issue of the Estonian youth workers´ professionality has been relevant for many years. Organizational factors are important in the youth worker´s professional growth. Youth worker is a promoter of non-formal education. Research explained the issues related to the youth workers professional growth, including organizational factors. The theoretical framework of the research created Ruohotie, Tamm concepts of professional growth and Hackman, Oldham job satisfaction characteristics. The purpose of this research was brought to the light youth work specialists´ opinions about the organizational factors of the professional growth. For qualitative data collection semi-structed interviews were conducted with 35 Estonian youth work specialists in 2016-2018. The results showed that in eight key-topics important opinions were received. Most attention should be given further to the beginner youth workers´ support for efficient and faster adaptation with work. Mostly were explained interviewees high satisfaction with team and colleagues. Interviews revealed a different commitment to work, which depends of the employee´s professional awareness and involvement in initiatives, that could have resulted from different education, professional training or personal characteristics. The quality of the feedback is important for the employee's professional growth. Individualisation of the work may create a threat to versatility. For further clarification: youth workers´ professional identity.